Survival after stereotactic radiotherapy in patients with early-stage non-small cell lung cancer. (3rd October 2019) - Hansen, Olfred; Kristiansen, Charlotte; Nielsen, Morten; Schytte, Tine; Starup Jeppesen, Stefan
Abstract: Introduction: Stereotactic radiotherapy (SBRT) is the treatment of choice for inoperable early stage non-small cell lung cancer (NSCLC). We report analyses of the influence of age on survival after SBRT. Methods and material : From 2005 to 2017, 544 previously un-irradiated patients with early stage NSCLC had SBRT. The data were analyzed in four age groups: A: –69 (176 pts), B: 70–74 (115 pts), C: 75–79 (131 pts) and D: 80 years or older (122 pts). Two SBRT dose regimes were used: 45 Gy/3F ( N  = 103) and 66 Gy/3F ( N  = 441). Results: All patients had a follow up (time to censoring, FU) of at least 16 months, the median FU being 48.0 months. The median age was 74.4 years. The overall survival (OS) was associated with age. The median OS was 50.7, 45.9, 45.4 and 33.0 months, and the 5-year OS was 45%, 32%, 33% and 18% in groups A, B, C and D, respectively. No difference was found between groups B and C, while OS in group A was significantly better than remaining groups, and the OS in group D significantly poorer. In multivariable analyses, OS was heavily influenced by age, Charlson's comorbidity index (CCI) and performance status (PS). For lung cancer-specific survival (LCSS), only increasing tumor diameter and PS were associated with poor survival. Conclusions: The OS was influenced by age, but the study suggests that a cut point of 75 year is inappropriate in evaluating the effect of old age on survival. Poor PS was associated with poor OS. CCI influenced OS, but not LCSS, which was only affected by PS and tumor size.